Melia azedarach L. (Meliaceae): Phytochemical Analysis and Evaluation of Antibacterial Activity of Fruit Extracts. - Phakamani Linda Masuku; Himansu Baijnath; Karishma Singh (Student's Journal of Health Research Africa)
Background